Feasibility of Integrated AKM Instrument for Problem Solving on Reaction Rate Factors: Kelayakan Instrumen AKM Terintegrasi Penyelesaian Masalah pada Faktor Laju Reaksi. - Dinda Putri Mugiani; Wiwi Siswaningsih; Febriati Dian Mubarokah (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
Feasibility of Integrated AKM Instrument for Problem Solving on Reaction Rate Factors. This study aims to produce an integrated Minimum Competency Assessment (AKM) instrument for problem-solving skills in the sub-material of factors that influence reaction rate that are worthy of being reviewed in terms of validity and reliability.. The method used is development and validation. The participants involved were 4 lecturers and 1 teachers as validators and 35 grade XI students at one of Bandung's public high schools as respondents. The resulting product consists of 25 reading literacy questions and 5 numeracy literacy questions. The product is declared valid based on content validity, while empirically shows 20 valid questions and 10 invalid questions. All questions are declared reliable with details of reliability values ​​for questions with a maximum score of 1 being 0.59, questions with a maximum score of 2 being 0.75, and for questions with a maximum score of 4 being 0.82.